2007
DOI: 10.1038/sj.eye.6702875
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy to replace the natural vitreous by a novel capsular artificial vitreous body with pressure-control valve

Abstract: Purpose The current vitreous substitutes such as silicone oil, heavy silicone oil, and polymeric gels that are directly injected into vitreous cavity frequently cause severe intraocular complications. There is a very urgent need to find a more suitable artificial vitreous substitute for pars plana vitrectomy (PPV) surgery. Methods We have devised a novel capsular artificial vitreous using tailor-made silicone rubber elastomer. The novel device was implanted into the vitreous cavity of rabbit after PPV and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 28 publications
0
62
0
Order By: Relevance
“…After foldable installation into the eye, a balanced salt solution (BSS) could be injected into the capsule and inflated to support the retina and control the intraocular pressure through the tube-valve system. 18 In the rabbit model of PVR, we found that the FCVB very closely mimicked the morphology and restored physiological functions, such as support, refraction, and cellular barriers during a 3-month observation period, without the obvious complications commonly induced with traditional silicone oil (see Supplemental Text 1). In addition, the FCVB changes the refraction very little when compared with silicone oil and heavy silicone oil, based on the Gullstrand-Emsley and Liou-Brennan schematic eyes.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…After foldable installation into the eye, a balanced salt solution (BSS) could be injected into the capsule and inflated to support the retina and control the intraocular pressure through the tube-valve system. 18 In the rabbit model of PVR, we found that the FCVB very closely mimicked the morphology and restored physiological functions, such as support, refraction, and cellular barriers during a 3-month observation period, without the obvious complications commonly induced with traditional silicone oil (see Supplemental Text 1). In addition, the FCVB changes the refraction very little when compared with silicone oil and heavy silicone oil, based on the Gullstrand-Emsley and Liou-Brennan schematic eyes.…”
Section: Introductionmentioning
confidence: 90%
“…In previous studies, we used a new strategy and rationale to fabricate the artificial vitreous substitute using FCVB [18][19][20] and first demonstrated that the FCVB can restore the structure and partial functions of a detached retina that are not easily reattached with silicone oil. 21 Patients in this predicament cannot obtain an intact eyeball and are forced to live with the outcomes of atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various substances and approaches have been explored, but to date, clinically available alternatives to conventional tamponades (gas and silicone oil) are still very limited. [12][13][14][15][16][17][18] Identifying and developing a novel intraocular tamponading agent is a challenging task, albeit with a large therapeutical potential. The first step of this approach is to determine if the agent would be toxic to the retina or other ocular tissues.…”
Section: Intraocular Pressurementioning
confidence: 99%
“…It is a thin, vitreous-shaped capsule made of a silicone rubber elastomer with a silicone tube valve system filled with a physiologically balanced solution or silicone oil. 41 The silicone rubber capsule has shown good biocompatibility and is easily implanted and removed experimentally in rabbit eyes. Over an 8-week treatment period, there was no corneal opacity, intraocular inflammation, or vitreal opacity but there was a high incidence of cataracts in the rabbit eyes, whether they were caused by the material of the FCVB or the lens structure of their eyes should be further evaluated.…”
Section: Implantsmentioning
confidence: 99%